Power management system for a fuel cell/battery hybrid vehicle incorporating fuel cell and battery degradation. (29th March 2019) - Wang, Yongqiang; Moura, Scott J.; Advani, Suresh G.; Prasad, Ajay K.
Abstract: Optimization of fuel cell/battery hybrid vehicle systems has primarily focused on reducing fuel consumption. However, it is also necessary to focus on fuel cell and battery durability as inadequate lifespan is still a major barrier to the commercialization of fuel cell vehicles. Here, we introduce a power management strategy which concurrently accounts for fuel consumption as well as fuel cell and battery degradation. Fuel cell degradation is quantified using a simplified electrochemical model which provides an analytical solution for the decay of the electrochemical surface area (ECSA) in the fuel cell by accounting for the performance loss due to transient power load, start/stop cycles, idling and high power load. The results show that the performance loss based on remaining ECSA matches well with test data in the literature. A validated empirical model is used to relate Lithium-ion battery capacity decay to C-rate. Simulations are then conducted using a typical bus drive cycle to optimize the fuel cell/battery hybrid system. We demonstrate that including these degradation models in the objective function can effectively extend the lifetime of the fuel cell at the expense of higher battery capacity decay resulting in a lower average running cost over the lifetime of the vehicle. Highlights: New power management system for a fuel cell/battery hybrid vehicle is developed. Both fuel cell and battery degradation are modeled to optimize power management. The simulated system lifetime is validated against previous experimental data. Optimization extends fuel cell life at the cost of higher battery capacity decay.